PREPOSISI DALAM BAHASA INGGRIS DAN BAHASA BUGIS (Suatu Analisis Kontrastif) - PRICILYA, FEMI; KODONG, FENTJE; LOTULUNG, DONALD R. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACT This research is entitled ‘Preposition in English and Bugis Language’ (A Contrastive Analysis). It is written to identify and classify the forms and analyze the meanings of preposition in English and Bugis language, and to find out the similarities and differences.The English data were taken from some grammatical books and English education journals FKIP UNS and the Bugis data have been collected by hearing Folktale and life experience in Bugis language from several informants in Manado and Makassar. In analyzing the data, the writer used theories of Bloomfield, Arts and Arts, Harman and theory of Lado to contrasting both languages.The result shows that preposition in English and Bugis language have similarities and differences in forms and meanings. The similarities can be found in meanings, both languages can indicates place, time, cause, tools and source. The differences are shown in the forms, English language has eight complex forms of preposition while Bugis language has no complex forms of preposition. Keywords: Preposition, English and Bugis Language, Contrastive Analysis.